Določitev geodetskega datuma mreže na plazu Urbas - Pleterski, Žan (Geodetski vestnik, 2022)
This article describes the geodetic network of the Urbas landslide. It is the largest landslide in the Koroška Bela region, which, if triggered, can endanger human lives and damage infrastructure. In order to monitor the landslide, a geodetic network was established in the area of the Urbas landslide, on the basis of which the movements of control points can be calculated. After various analyses, only two small areas near the Urbas landslide proved to be stable, so we established four reference points there. In this research we defined the geodetic datum of the geodetic network of the Urbas landslide. The geodetic datum was defined on the basis of four measurement epochs processed with our own software.
Keywords: geodetska mreža; geodetski datum; girusna metoda; izravnava geodetske mreže; plaz Urbas; stabilnost referenčnih točk